PENGARUH LIKUIDITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN (Studi Empiris pada Perushaan Manufaktur yang terdaftar di BEI Pada Periode Tahun 2016-2018) - Anita Rachman; Afifudin Afifudin; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The purpose of the audit is to provide an objective assessment, impartiality and clarify the level of suitability of financial statements in a company. The results of the audit can be seen that the company's condition in reporting and financially can meet the company's survival or not. Companies that get going concern audit opinion are companies that have problems in finance, inability to pay interest, and a bad liquidation process. The issuance of going concern audit opinion will have an impact on the loss of public confidence in the company's image and company management. This will affect the continuity of business in the future. This study aims to determine the effect of liquidity and company growth on the provision of going concern audit opinion on manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2018 period. The method of data collection in this study uses secondary data sources in the form of annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period of 2016-2018. This study uses purposive sampling with a total sample of 30 companies. The analytical method in this study uses the logistic regression method with SPSS 20 statistical software. Based on the test results, the liquidity and growth variables of the company simultaneously affect the going concern audit opinion. Partially, it can be concluded that liquidity has an influence on the going concern audit opinion. Meanwhile, company growth does not have a significant effect on going-concern audit opinion. Based on these results, companies and investors need to pay attention to the composition of the company's liquidity level. So the company can convince shareholders, and investors can minimize risk when investing.Keyword: Liquidity, Company Growth and Going Concern Audit Opinion.